The relationship between obstructive sleep apnea and visual hallucinations in PD patients: a polysomnography study - Zhu, Jun; Zhao, Yang; Jiang, Yinyin; Pan, Yang; Jiang, Xu; Wang, Yaxi; Li, Dongfong; Zhang, Li (Frontiers in Neurology, 2024)
Purpose Parkinson's disease (PD) patients frequently experience visual hallucinations (VHs) and obstructive sleep apnea (OSA). The aim of this study was to describe the prevalence and clinical correlates of VHs and OSA in the Chinese population with PD. Materials and methods A sample of 489 PD patients was recruited for the present study. Patients were categorized as having formed VHs (FVHs) or minor VHs (MVHs) or as non-hallucinators (NVHs) according to the Unified Parkinson's Disease Rating Scale (UPDRS) and an initial questionnaire. Polysomnography (PSG) was used for objective assessment of sleep. Results VHs were observed in 143 (29.2%) patients. Among them, 75 of the hallucinators experienced MVHs, and 68 experienced FVHs. The disease duration, UPDRS Part III score, Hoehn and Yahr (H–Y) stage, Pittsburgh Sleep Quality Index (PSQI) score and rapid eye movement (REM) sleep behavior disorder (RBD) score of hallucinators were significantly greater than those of non-hallucinators (P < 0.05). We also observed OSA in 38.7, 54.7, and 63.3% of the NVH, MVH, and FVH groups, respectively. PSG showed that the VH groups had a lower total sleep time, lower sleep efficiency, higher arousal index, lower sleep latency, lower N1%, higher apnea-hypopnea index (AHI), higher average duration of apnea, higher respiratory-related arousal (RRA), and lower values of the lowest O2 and mean O2. The forward binary logistic regression model showed that AHI, N1%, RRA and lowest O2 were independently associated with VHs in PD patients. Conclusions Our results confirm the high prevalence of VHs and OSA as well as their relationship in patients with PD.